Diagnosis of Respiratory Tract Infection and the Use of the Laboratory - Ronald F Grossman (Canadian Journal of Infectious Diseases)
Lower respiratory tract infections continue to be among the most common illnesses requiring medical attention with considerable morbidity and morality. Clinical features, including underlying conditions, presenting signs and symptoms, basic laboratory investigations and chest roentgenograms, are not sufficiently precise to infer an etiological agent. These investigations do permit an assessment of severity of illness and can assist in stratification of patients into high risk groups. Properly performed and interpreted Gram stain of sputum is still useful in the initial assessment of these patients, but sputum cultures are less helpful. Blood cultures should be drawn in patients ill enough to require hospitalization, but the yield is low, Pneumococcal antigen testing and serological studies do not add to the routine management of patients with pneumonia. In patients with nosocomial pneumonia, the diagnosis will be established by a synthesis of clinical, roentgenographic and simple laboratory results such as sputum analysis and blood culture. Invasive investigations should be reserved for critically ill patients.